Proteomic And Biochemical Analysis Of Detoxification Enzyme In Musca Domestica L. (Diptera: Muscidae) And Its Response Upon Prolonged Exposure Of Insecticide - Manoharan, Kalaavathi (2024)
This study provides the proteomic and biochemical information of the detoxification enzymes namely acetylcholinesterase (AChE), α-esterase (α-est), β- esterase (β-est), glutathione s-transferase (GST) and cytochrome P450 (Cyt P450) in susceptible (adult, larvae and pupae) and poultry strains (larvae) Musca domestica. Upon whole protein analysis, number of proteins discovered in larvae was highest (441), followed by adults (181) and pupae (115) which concluded specific proteins are necessary for the proper progression of each developmental phase. Meanwhile, the enzyme activities as well as the protein content of the susceptible strain were found to have significantly varied enzymatic activity across the developmental stages (p<0.05). Thirthy four distinct peptides of the targeted detoxification enzyme were discovered at various developmental stages of the susceptible strain. Functional analysis of the targeted peptides of the susceptible strains exposed that in addition to their functions in detoxification, the multifunctional enzymes were also found to be developmental-related proteins that responsible in various biological process, molecular functions and KEGG pathways to complete metamorphosis. Overall, it has been observed that at the larvae stage, the targeted developmental related detoxification peptides were more expressed and were the most enriched in terms of biological process, molecular function and KEGG